Formation of Profession “Business Analyst” in Russia - Yu. G. Chernysheva (International Business and Accounting Research Journal, 2019)
The article considers the aspects of forming and developing business analyst profession in Russia. It describes the main issues and reasons of using the analysis by Russian companies at little extent. The author reveals the significance of the analysis for managerial decision-making as well as the content of business analysis concept, basic and key terms of business analysis and their interactions. The content of business analyst profession is examined in accordance with occupational standard and international practice. The article also describes the features and differences of new business analysis concept from analysis techniques existing in Russia.